Scoping Review: The Role of Psychedelics in the Management of Chronic Pain - Robinson CL; Fonseca AC; Diejomaoh EM; D'Souza RS; Schatman ME; Orhurhu V; Emerick T (Journal of Pain Research, 2024)
Christopher L Robinson,1,* Alexandra CG Fonseca,2,* Efemena M Diejomaoh,3,* Ryan S D’Souza,4 Michael E Schatman,5,6,* Vwaire Orhurhu,7,8,* Trent Emerick9,* 1Beth Israel Deaconess Medical Center, Department of Anesthesiology, Critical Care, and Pain Medicine, Harvard Medical School, Boston, MA, USA; 2Department of Anesthesiology, Perioperative & Pain Medicine, Harvard Medical School, Brigham & Women’s Hospital, Boston, MA, USA; 3Department of Psychiatry & Behavioral Science, Meharry Medical College, Nashville, TN, USA; 4Department of Anesthesiology and Perioperative Medicine, Mayo Clinic Rochester, Rochester, MN, USA; 5Department of Anesthesiology, Perioperative Care, and Pain Medicine, NYU Grossman School of Medicine, New York, NY, USA; 6Department of Population Health-Division of Medical Ethics, NYU Grossman School of Medicine, New York, NY, USA; 7University of Pittsburgh Medical Center, Susquehanna, Williamsport, PA, USA; 8MVM Health, East Stroudsburg, PA, USA; 9University of Pittsburgh Medical Center, Department of Anesthesiology and Perioperative Medicine, Chronic Pain Division, Pittsburgh, PA, USA*These authors contributed equally to this workCorrespondence: Vwaire Orhurhu, University of Pittsburgh Medical Center, Susquehanna, Williamsport, PA, USA, Email vwo569@mail.harvard.eduIntroduction: Amid a lack of effective chronic pain treatments, psychedelics have gained attention as a potential solution, although their Schedule 1 classification poses challenges. Psychedelics, such as lysergic acid diethylamide (LSD) and psilocybin, have gained popularity as alternatives and adjuncts for chronic pain treatment. Studies suggest that they may modulate pain processing through agonism primarily at the serotonin receptor, 5-HT2A. One of the first of its nature, we present an artificial intelligence (AI)-powered scoping review primarily focusing on evaluating psychedelics for chronic pain conditions such as cluster headache, phantom limb pain, and fibromyalgia.Methods: In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we used an AI-powered comprehensive search strategy utilizing the ChatGPT4.0 Bing chat to search Medline, Embase, Cochrane, and Google Scholar for articles addressing chronic pain. The query was performed on June 1, 2023, focusing on psychedelics for chronic, non-cancer pain including headache disorders. Inclusion criteria were English-only, peer-reviewed articles involving human participants > 18 years, focusing on chronic pain conditions (eg, phantom limb pain and cluster headache), using LSD, 2.5-dimethoxy-4-bromophenethylamine (2C-B), N, N-dimethyltryptamine (DMT), psilocybin, or mescaline. Exclusion criteria were reviews, editorials, and opinion articles and studies focusing on tetrahydrocannabinol/cannabis and/or ketamine.Results: A total of 186 unique database entries were retrieved, of which nine studies were included in the scoping review. These included four case reports/series, an open-label study, a cohort study, two online surveys, and a randomized, double-blind, placebo-controlled trial. They comprised three studies addressing phantom limb pain, four addressing cluster headaches, and two addressing fibromyalgia, spinal cord injury, complex regional pain syndrome, and lumbar radiculopathy.Conclusion: Psychedelics may have potential in alleviating pain symptoms secondary to a multitude of chronic pain conditions. However, further randomized, double-blind, placebo-controlled trials are needed to further explore and evaluate the role of psychedelics in chronic, non-cancer pain.Keywords: psilocybin, mescaline, lysergic acid diethylamide, headache, phantom limb pain, scoping review